Empoderamento de meninas para defesa dos direitos e equidade de gênero: intervenção em grupo - Augusti, Vitória da Silva (Universidade Federal de São Carlos, 2019)
Empowerment is a change in the experience of power achieved by an individual in their interaction with the social world, the present study will perform a group intervention with girls aiming at empowerment in their diverse values. The participants were eleven girls in the first group and six girls in the second group, aged between 10 and 12 years old. To evaluate the effectiveness of the intervention the response measures of the instruments applied before and after the intervention will be compared, also the girls' speeches during the encounters will be analised. Thus, it aims to evaluate the effects of an intervention aimed at empowering, raising awareness and increasing repertories of sources in question. In conclusion, the results sugest that the intervention was effective to provide information about children’s and teenagers rights, sexual and reproductive right’s of girl’s, also, promoting the debate about gender.
Girls' empowerment to defend gender rights and equity: group intervention
Keywords: Empoderamento; Intervenção em grupo; Direitos humanos; Empowerment; Group intervention; Human rights; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA